1996
DOI: 10.1183/09031936.96.09030422
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive mechanical ventilation improves the immediate and long-term outcome of COPD patients with acute respiratory failure

Abstract: N No on ni in nv va as si iv ve e m me ec ch ha an ni ic ca al l v ve en nt ti il la at ti io on n i im mp pr ro ov ve es s t th he e i im mm me ed di ia at te e a an nd dl lo on ng g--t te er rm m o ou ut tc co om me e o of f C CO OP PD D p pa at ti ie en nt ts s w wi it th h a ac cu ut te e r re es sp pi ir ra at to or ry y f fa ai il lu ur re e M. Confalonieri*, P. Parigi*, A. Scartabellati*, S. Aiolfi*, S. Scorsetti*, S Nava**, L. Gandola* In-hospital survival rate was not significantly different in Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
3
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 37 publications
5
53
3
5
Order By: Relevance
“…The duration of invasive mechanical ventilation was 13±6 days (range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in the 4 patients in the treatment group who required reintubation and who had favourable outcomes. In the surviving patients, the total time of ventilatory assistance for the treatment of the postextubation distress (duration of NIPSV in all patients in the treatment group, and duration of invasive mechanical ventilation performed after reintubation in patients in both groups who required reintubation) was 6±4 days (range, 2-21) in the treatment group compared with 11±8 days (range, 5-25) in the control group (p<0.01).…”
Section: Clinical Studymentioning
confidence: 99%
“…The duration of invasive mechanical ventilation was 13±6 days (range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in the 4 patients in the treatment group who required reintubation and who had favourable outcomes. In the surviving patients, the total time of ventilatory assistance for the treatment of the postextubation distress (duration of NIPSV in all patients in the treatment group, and duration of invasive mechanical ventilation performed after reintubation in patients in both groups who required reintubation) was 6±4 days (range, 2-21) in the treatment group compared with 11±8 days (range, 5-25) in the control group (p<0.01).…”
Section: Clinical Studymentioning
confidence: 99%
“…In the study of BOTT et al [4], NIPSV was used for 6 days, as for patients in group I in the present study; however, respiratory acidosis was more significant for patients in the present study than in that of BOTT et al [4]. Some authors have previously proposed administering NIPSV discontinuously [1,4,5,20,23,24]. The sequential mode used on the present study is also a discontinuous mode, thus allowing comparison of the present results with those of other studies, with some specificity, i.e.…”
Section: Discussionmentioning
confidence: 50%
“…4 days. Conversely, in the study of CON-FALONIERI et al [20], the patients were ventilated for 9.8 days, despite the fact that the technique was used continually. In the study of BOTT et al [4], NIPSV was used for 6 days, as for patients in group I in the present study; however, respiratory acidosis was more significant for patients in the present study than in that of BOTT et al [4].…”
Section: Discussionmentioning
confidence: 99%
“…Acidosis is associated with increase mortality and also a higher need for intubation.2 3 Noninvasive ventilation (NIV) using a face or nasal mask has been shown in randomized controlled trials to reduce the need for subsequent intubation and mortality in this group of patients.4-6 Two cohort studies have also reported a long term survival advantage [19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Total admission rates fall in the summer but the rate of respiratory acidosis was more constant at 18 per month (range [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Variability In Admission Rates Within and Between Yearsmentioning
confidence: 99%